Effect of beef tallow on growth performance, carcass characteristics, meat composition, and lipid profile of growing lambs - Ahmed, Shahana; Khatun, Jannatara; Islam, Md. Manirul; Khan, Md. Kabirul Islam; Mahmud, S. M. Niaz; Al Noman, Md. Abdullah; Islam, Md. Zohorul (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of this study was to investigate the effect of diets with inclusion of beef tallow on growth, and carcass characteristics, meat quality, and lipid profile in growing lambs. The experiment was conducted with 15 lambs for 63 days. The lambs were randomly allotted into three dietary treatments (T0, T1, and T2) with five animals in each group; T0 (control diet without beef tallow), T1 (diet with 2% beef tallow), and T2 (diet with 4% beef tallow). The body weight and feed conversion ratio (FCR) were significantly (P<0.05) increased in T1 group as compared to other groups. Dressing percentages of warm carcass in T0, T1 and T2 group were 43.93, 42.87 and 44.05%, respectively. There were no significant differences (P>0.05) on meat quality and chemical composition among the three dietary groups. Group T1 showed the highest increase of cholesterol concentration (11.5%) at the end of experiment, but serum triglyceride concentration was not significantly (P>0.05) correlated with any of the three dietary groups. To sum up, the use of beef tallow at 2% level in lamb diet can increase their performance without having any deleterious effect on carcass, meat quality and lipid profile. DOI: http://dx.doi.org/10.5455/javar.2015.b96